Nurse led care coordination: Trial protocol and development of a best practice resource guide for a cluster controlled clinical trial in Australian aged care facilities - Arendts, G.; Etherton-Beer, C.; Howard, K.; Lewin, Gill; Sim, M.; Pickstock, S.; Fitzhardinge, S.; O'Brien, K.; Tassell, S.; Deans, P.; Blackwell, S. (Elsevier Ireland Ltd, 2014)
In this paper we describe (i) the protocol for a cluster controlled clinical trial of nurse led care coordination in residential aged care facilities (RACF); and (ii) the development and content of a best practice resource guide to be implemented as part of this trial. We used published systematic reviews of quantitative studies, existing resources and multidisciplinary expert opinion to develop an intervention for testing in a cluster controlled trial (Australian and New Zealand Clinical Trials Registry Number 12611000933954). The trial will determine whether care coordination of multiple evidenced based strategies can improve quality of life and reduce hospitalization rates amongst people living in RACF. Central to the intervention arm of the trial are two components: (i) experienced nurse practitioners responsible for resident care and (ii) a best practice guide for the care processes being delivered and coordinated by those nurses. In this paper we outline how this practice guide, which is published herein, was refined through consultative processes and practitioner testing.